Modeling And Simulation of A Conceptual Reaction Coupling System For Ammonia-Urea Production - CHIAH , YOKE YI (2017)
Cost and energy efficiency improvements through the reaction coupling of ammonia and urea can help to reduce the cost of food production. The existing rigorous models contain more parameters, variables, and equations. Thus, rigorous models consume more time and require greater computational efforts besides being more rigid for the simulation of any significant change from the base case